THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) ON CONSUMER ELECTRONICS - Dr. K. Sudha Ramya; G. Yogeswar Rao (The Bioscan, 2024)
Artificial intelligence (AI) significantly impacts consumer electronics by making devices more intuitive, personalized, and efficient, enabling them to learn from user behavior, optimize performance, and automate routine tasks, ultimately enhancing the overall user experience across various applications like smart homes, wearables, and communication tools; however, concerns around data privacy and security remain crucial considerations when integrating AI into consumer electronics. AI improves the computational capabilities of consumer electronics by incorporating complex algorithms that can learn and adapt based on data. These algorithms range from simple predictive models used in personalizing user interfaces to sophisticated neural networks that enable advanced image and speech recognition.